2019
DOI: 10.1038/s41467-019-12097-6
|View full text |Cite
|
Sign up to set email alerts
|

Human immunoglobulin G hinge regulates agonistic anti-CD40 immunostimulatory and antitumour activities through biophysical flexibility

Abstract: Human immunoglobulin G (IgG) agonistic antibodies targeting costimulatory immunoreceptors represent promising cancer immunotherapies yet to be developed. Whether, and how, human IgG hinge and Fc impact on their agonistic functions have been disputed. Here, we show that different natural human IgGs confer divergent agonistic anti-CD40 immunostimulatory and antitumour activities in FcγR-humanized mice, including inactive IgG3 and superior IgG2. This divergence is primarily due to their CH1-hinges despite all hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 55 publications
3
37
0
Order By: Relevance
“…Additionally, the hinge region in the CH1 domain is also important and required for antibody agonistic function. The more rigid the hinges of a given IgG, the more stable the clustering of the immunostimulatory receptors on cell membranes and thus the greater the anti-tumor efficacy [45]. Replacement of the hinge region with that of IgG3 completely eliminated the anti-tumor activity of the anti-CD40 antibody, although both the CD40 and the FcγR binding affinity were retained.…”
Section: Selection Of Igg Subclasses For Targets Expressed In Immunementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the hinge region in the CH1 domain is also important and required for antibody agonistic function. The more rigid the hinges of a given IgG, the more stable the clustering of the immunostimulatory receptors on cell membranes and thus the greater the anti-tumor efficacy [45]. Replacement of the hinge region with that of IgG3 completely eliminated the anti-tumor activity of the anti-CD40 antibody, although both the CD40 and the FcγR binding affinity were retained.…”
Section: Selection Of Igg Subclasses For Targets Expressed In Immunementioning
confidence: 99%
“…Even for the engineered IgG1-Fc with enhanced binding affinity to FcγRIIB [46], the original potent anti-tumor activity was completely lost. However, when combining the rigid hinge region with an engineered Fc domain stronger for FcγRIIB binding, anti-tumor activity significantly improved [45], indicating human CH1-hinge regions, selected for rigidity, and Fc domains engineered for FcγRIIB engagement can synergize to enhance the immunostimulatory and anti-tumor activities of antibodies targeting TNFR superfamily members.…”
Section: Selection Of Igg Subclasses For Targets Expressed In Immunementioning
confidence: 99%
“…In contrast, agonism of an IgG2 mAb, such as CP-870,893, is believed to be provided by its unique hinge conformation ( 54 , 55 ). A recent study demonstrated that hinge rigidity and selective FcγR binding affinity are both critical in regulating antibody agonistic function ( 56 ). In addition, other research has shown that the binding site is important in determining CD40 mAb agonistic activities, as membrane CRD1-binding displays stronger agonistic activities when the binding site is distal to the membrane than when it is proximal ( 57 ), and this relationship between binding epitope specificity and agonistic activity varies in TNFRs and needs to be resolved on a case-by-case basis ( 58 ).…”
Section: The Profiles Of Agonistic Antibodies Targeting Cd40 For Cancmentioning
confidence: 99%
“…The degradation of the electrochemical performance resultsf rom increased electrode resistance (electrical and ionic) and restricted charge transport. [13] Therefore, it is essential to develop an efficient preparation route to achieve ah ighere nergy-storage capacity for high-mass-loaded electrodes. Owing to the 2D layered structure, highers urfacea rea, and facile ion transportation path, 2D pseudocapacitive electrode materials have shown promise for use in SCs.…”
Section: Introductionmentioning
confidence: 99%